Two new species of Valleriola (Hemiptera: Heteroptera: Leptopodidae) and taxonomic notes on the tribe Leptopodini Brullé, 1836 from East and Southeast Asia - Li, Zihe; Jin, Zezhong; Polhemus, Dan A.; Ye, Zhen (Zootaxa, 2023)
Two species of the genus Valleriola Distant, 1904 (Heteroptera: Leptopodomorpha: Leptopodidae: Leptopodinae: Leptopodini) are described as new: Valleriola asiatica sp. nov. from Laos and Hainan Island of China, and Valleriola bui sp. nov. from Laos and Thailand. In addition, Leptopus riparius Hsiao, 1964 is newly recorded for Vietnam, Valleriola javanica Drake & Hottes, 1951 is newly recorded for Laos, and additional records are provided for Leptopus riparius, Valleriola javanica and Valleriola buenoi (Usinger, 1942). Photographs of the dorsal habitus, heads, hemelytra, fore femora, male parameres and live specimens are provided, accompanied by a distribution map for the species of Leptopodini occurring in East and Southeast Asia.